KEBIASAAN MAKAN SAYUR DAN BUAH PADA PETANI YANG BERKAITAN DENGAN KEJADIAN KATARAK DI KECAMATAN TELUK JAMBE JAWA BARAT - Mihardja, Laurentia; Tana, Lusianawaty; Ghani, Lannywati (PERSATUAN AHLI GIZI INDONESIA, 2008)
RISK OF CATARACT ASSOCIATED WITH FRUIT AND VEGETABLE INTAKE AMONG FARMERS OF WEST JAVARisk for cataract increases with age, but also has been associated with exposure to sunlight, andfactors such as smoking, and diet. We explored the risk of cataract in West Java, and found a strongassociation with diet, and a higher risk among malnourished adults. The aim of the study was to knowthe relationship between risk of c ataract and consumption of fruit and vegetables intake among farmersof West Java. This study using cross sectional design which was conducted among farmers and theirfamilies in West Teluk Jambe subdistrict, Karawang West Java, Indonesia. Randomly sampledindividual 30 years and older in the population and identified 1223 subjecs to participated in the study.Each subject was interviewed about vegetables and fruit consumption per day and per week previouslyand historical quantity of intake by use of questionnaire and food models. Anthropometry measurement(weight and height) were also undertaken. Ocular examinations were carried out by opthalmologist.The results showed that risk of cataract increases by age. The subjects for >55 years vs 30 – 54 yearsold give an odds ratio of 30.6.( 95% CI: 22.04- 42.5, p= 0.0001). Consumption of vegetables < 5serving vs = 5 serving perday had a significant odds ratio for cataract risks of 1.74 ( 95% CI: 1.04-2.91, p= 0.031). Intake of colourfull fruits had a similar odds ratio for < 1 serving vs = 1 serving per daywith an odds ratio for cataracts risks of 1.74 (95% CI: 1.26 – 2.4, p=0.001). Underweight (body massindex < 18.5) vs with > or = normal body weight was also very important with an odds ratio of 4 ( 95%CI: 3.2 – 5.8, p= 0.0001). Using binary logistic regression only ages, and nutritional status showed asignificant relationship with cataract risk. This study demonstrates that consumption of vegetables andfruits >5 serving per day, intake colourfull fruits >1 serving per day and having good nutrition withstatus BMI normal can reduce the risk for cataracs. To prevent cataracts it is important to promote theconsumption of vegetables and fruits, colourful fruit and to promote good nutritional status.Key words: cataract, fruit, vegetable, underweight